Knowledge management and professional skills of the teachers from an educative network of Lima - Torres V., Manuel (2017)
As the knowledge management has acquired a significant importance as a change and development factor in all the work of the society, it is vital to create a culture where information and knowledge are valued, shared, managed and used effective and efficiently. Under these considerations, the current investigation is made, having as main objective to establish whether the knowledge management has influence on the professional skills in a sample of teachers from an Educative Network of Lima Metropolitana. A correlational causal design was used with a sample of 217 to whom two instruments of evaluation were applied: the Questionnaire of Knowledge Management of Liliana Pedraja and the Inventory of Teaching skills of Úrsula Romaní. The analyses the instruments were submitted to determined consistent levels of validity and reliability. The results show that the Knowledge Management has significant influence on the Professional skills of the teachers (F = 18,136, p < ,001). Moreover, it is possible to appreciate in the results that the cited variables are correlated in its totals and its dimensions, so it is posible to affirm that all the planted objectives were met.